Competitive hydrogen bonding induced phase separation in supramolecular comb-shaped diblock copolymer. (14th March 2022) - Xu, Xiangyun; Zhou, Youshuang; Gao, Yutong; Liu, Xinlu; Chen, Shenbin; Xiong, Bijin; Wang, Yingying; Zhu, Jintao
Abstract: In this study, a route to prepare nanostructure in miscible diblock copolymers by utilization of competitively intermolecular hydrogen-bonding interactions is demonstrated. Block copolymers poly(4-vinylpyridine- b -4-hydroxybutyl acrylate) (P4VP- b -P4HBA) with various block ratios were synthesized and they were demonstrated to be miscible due to the intramolecular hydrogen bonding. By combination of P4VP- b -P4HBA and 3-pentadecylphenol (PDP), the miscible block copolymer forms comb-shaped di-block copolymer complexes through the competition interactions between the hydroxyl groups of PDP (proton donors) and the nitrogen of the pyridine rings of the P4VP blocks (proton acceptors). Upon blending with PDP, we observed morphology change from sphere structure to cylindrical, and lamellar, in a manner strongly dependent on the P4HBA fraction. The microstructure of this special comb-shaped di-block copolymer shows a strong sensitivity to the temperature. The results from the in situ small angle X-ray scattering experiments have demonstrated that, even below the order-disorder temperature, the size of the phase domain decreases with increasing temperature due to decrease of the strength of the hydrogen bond upon heating. Graphical abstract: Image 1 Highlights: Miscible block copolymers were synthesized via RAFT polymerization. Microphase separation was induced by competitive hydrogen bonding. Temperature dependence of competitive hydrogen bonding induced microphase separation was investigated.